Average daily gain of local pigs on rural and peri-urban smallholder farms in two districts of Western Kenya - Carter, Natalie A.; Dewey, Catherine E.; Mutua, Florence K.; Lange, C.F.M. de; Grace, Delia (Springer, 2013)
The objective of this study was to determine the average daily gain (ADG) of pigs on rural and peri-urban smallholder farms in two districts of Western Kenya, in order to establish a baseline to measure the impact of future management interventions. Average daily gain (kilograms per day) for 664 pigs weighed one, two or three times and the proportion of local and crossbreed pigs was determined. Assuming a uniform birth weight of 1 kg, ADG did not differ between pigs weighed once or twice. Overall, ADG was higher in peri-urban pigs (0.15 ± 0.058 kg/day) than rural pigs (0.11 ± 0.047 kg/day). Pigs at 1 to 2 months had a higher ADG than those at 3 months or 10 to 12 months and ADG was higher in crossbreed than local pigs. Over the two districts, the ADG was low (0.13 ± 0.002 kg/day). Most (87.2 %) pigs were of local breed. Low ADG may be due to malnourishment, high maintenance energy expenditure, high parasite prevalence, disease, and/or low genetic potential. This low ADG of pigs raised on smallholder farms in Western Kenya indicates a high potential for improvement. The growth rate of pigs in Western Kenya must be improved using locally available feedstuffs to make efficient use of resources, promote sustainable smallholder pig production, and improve the livelihood of smallholder farmers.